1,3,4-THIADIAZOLE AND ITS DERIVATIVES: AN OVERVIEW ON CRYSTAL STRUCTURE AND TRIBOLOGY ACTIVITIES - ABDUL BASIR, NURUL FATIMAH; ABDUL WAHAB, YASMIN; JOHAN, MOHD RAFIE; KHALIGH , NADER GHAFFARI (Malaysian Catalysis-An International Journal, 2022)
1,3,4-thiadiazole derivatives has been attracted great attention due to application in various areas. Synthesis and crystal structure is briefly investigated. Their application in high temperature and high pressure as anti-friction and antiwear, and improve the anti-wear and extreme pressure properties have been described. The effect of various 1,3,4-thiadiazole additives on the tribological properties of base oils is studied. This paper aims to present an overview of the role of 1,3,4-thiadiazole and its derivative in improving the tribological properties of base oils.